Penerapan Organisasi Pembelajar Dalam Upaya Meningkatkan Kinerja PD ABC - Hendriani, Rulli; Ma'arif, M. Syamsul; Affandi, M. Joko (Jurnal Borneo Administrator, 2018)
This study aims to 1) analyze the implementation of learning organization in PD ABC; 2) analyze the influence of learning organization towards performance improvement of PD ABC; 3) analyze the influence of leadership and organizational culture towards learning organizations, 4) analyze the influence of learning organization, leadership and organizational culture towards performance improvement of PD ABC, and 5) formulate a sustainable learning organization strategy to improve the performance of PD ABC. Methods in this research were Structural Equation Model (SEM) and Analytical Hierarchy Process (AHP). The results showed that 1) information systems and sharing of knowledge, organizational relationship, strategic leadership, collaboration and team learning need to be improved; 2) leadership has a positive influence and significant effect with learning organization but organizational culture has insignificant effect towards learning organization; 3) learning organization has a positive influence and significant effect towards improving PD ABC performance; learning organization has a positive influence and significant effect towards organizational performance, although leadership and organizational culture have a negative influence but insignificant effect towards performance organization; 4) in order to develop sustainable learning, PD ABC has to provide measurable evaluation and monitoring systems, transparent rewards and punishment, as well as competent people. Keywords: Leadership, learning organization, organizational culture, organizational performance, strategy Abstrak Penelitian ini bertujuan 1) menganalisis penerapan organisasi pembelajar di PDABC; 2) menganalisis pengaruh organisasi pembelajar terhadap organisasi pembelajar, 3) menganalisis pengaruh kepemimpinan dan budaya organisasi dengan organisasi pembelajar; 4) menganalisis pengaruh organisasi pembelajar, kepemimpinan, dan budaya organisasi terhadap peningkatan kinerja PD ABC; dan 5) memformulasikan strategi organisasi pembelajar berkelanjutan dalam upaya meningkatkan kinerja PD ABC. Metodologi penelitian ini mengambil data secara stratified random sampling ,analisadeskriptif,StructuralEquationModel (SEMLisrel), danAnalyticalHierarchy Process (AHP). Hasil penelitianadalah 1) sistem informasi dan penyebaran pengetahuan, hubungan organisasi,kepemimpinan strategis, kolaborasi dan pembelajaran tim masih perlu ditingkatkan; 2)kepemimpinan berpengaruh signifikan terhadap organisasi pembelajar, budaya organisasiberpengaruh tidak signifikan terhadap organisasi pembelajar; 3) organisasi pembelajarberpengaruh signifikan dengan kinerja organisasi, namun kepemimpinan dan budayaorganisasi secara langsung berpengaruh negatif namun tidak signifikan dengan kinerjaorganisasi 4) strategi meningkatkan kinerja PDABC melalui organisasi pembelajar yaitumenyediakan sistem evaluasi dan monitoring yang terukur serta reward dan punishment yangtransparan. Efektivitas kerja perlu didukung dengan penempatan orang yang tepat sesuai dengan kompetensinya dan melakukan pemberdayaan karyawan.Kata Kunci : Budaya organisasi, kepemimpinan, kinerja organisasi, organisasi pembelajar, strategi